The Impact of Managers’ Emotional Intelligence on Employees’ Work Life Balance: A Field Study at Jordanian Private Hospitals - Abu Bakir, Sahar Moh’d (European Scientific Journal, ESJ, 2018)
This paper focuses on testing the impact of managers’ emotional intelligence on employees work life balance in Jordanian private hospitals. 6 out of 13 hospitals were randomly selected, and 300 employees from nonmanagerial levels were surveyed using the questionnaire. 286 questionnaires were also analyzed. The most important findings of the study show that the managers in the examined hospitals have emotional intelligence skills, and the studied hospitals provide their employees with work life balance activities. The results of multiple regression revealed that there is a statistically significant impact of managers’ (empathy and social skills) on employees’ work life balance. The study revealed that there are differences of respondents’ perception of work life balance initiative due to their gender, while there are no differences of employees’ perception due to their marital status and number of children. Based on the results, the researcher recommended that more attention should be given to boost managers and employees emotional intelligence skills, and to broaden the scope of the provided work life balance activities in health care organizations and hospitals in particular.